XN-1000 Hematology Analyzer as an Alternative to Flow Cytometry for Measuring Residual Cells in Blood Components - Siller, Anita; Seekircher, Lisa; Schmidt, Daniela; Tschiderer, Lena; Willeit, Peter; Schennach, Harald; Amato, Marco (Annals of laboratory medicine, 2025)
Measuring residual cells in blood products is legally required for monitoring the manufacturing process and ensuring recipient safety. We compared the accuracy and performance of the two methodologies. Residual white blood cells (rWBCs), red blood cells (rRBCs), and platelets (rPLTs) were measured in RBC concentrates (rWBCs), fresh frozen plasma (rWBCs, rRBCs, and rPLTs), and PLT concentrates (rWBCs and rRBCs) using the Sysmex XN-1000 hematology analyzer (Sysmex, Kobe, Japan) equipped with Blood Bank mode and standard flow cytometry (fluorescence-activated cell sorting; FACS). rWBC counts in RBC concentrates and plasma were similar between XN-1000 and FACS. In pooled pathogen-inactivated PLT concentrates, XN-1000 yielded higher rWBC counts. Correlations between XN-1000 and FACS were moderate for rWBCs (0.42, 95% confidence interval: 0.15-0.69) in RBC inline-filtrated WBC-depleted RBC concentrates. In plasma, correlations were high for rWBC, rRBC, and rPLT counts, with Spearman correlation coefficients of 0.82-0.97. In pathogen-inactivated PLT concentrates, correlations were moderate for rWBCs (0.58, 0.33-0.84) and rRBCs (0.61, 0.35-0.87) in pooled samples but not significant in apheresis-derived samples. Median differences between FACS and XN-1000 were generally low, but XN-1000 overestimated residual cell counts in a subset of measurements. Residual cell cut-off values were surpassed in >90% of RBC concentrates, plasma, and apheresis pathogen-inactivated PLT concentrates using both methods. In pooled pathogen-inactivated PLT concentrates, 91.2% and 70.6% surpassed the cut-off using FACS and XN-1000, respectively. Sysmex XN-1000 is suitable for residual cell measurements in RBC concentrates and plasma, with some limitations for PLT concentrates.